Analysis of Factors Affecting Audit Report Lag with Audit Quality as a Moderating Variable in Consumer Cyclicals Companies Listed on the Indonesia Stock Exchange in 2021–2023 - Syakira, Rizka Febry; winda, winda (JURNAL MANAJEMEN MOTIVASI, 2025)
This study analyzes internal factors affecting audit report lag (ARL) in consumer cyclicals sector companies listed on the IDX during 2021–2023, and examines audit quality as a moderating variable. Data from 70 companies were analyzed using moderated regression. Results show that only company size has a significant positive effect on ARL, while audit quality moderates the effect of leverage on ARL. These findings underscore the importance of firm characteristics and audit quality in improving the timeliness of financial reporting, with implications for management to accelerate the audit process and for regulators to enhance market transparency.